Post-transcriptional regulation of organ-specific expression of individual rbcS mRNAs in Lemna gibba. - Silverthorne, J (1990)
Many studies of nuclear genes encoding chloroplast proteins have focused on the transcriptional regulation of their expression. The genes (rbcS) encoding the small subunit (SSU) of ribulose-1,5-bisphosphate carboxylase/oxygenase, a major stromal protein, comprise one such group. We have examined the role played by post-transcriptional events in determining the relative levels of individual rbcS mRNAs in different organs of the aquatic monocot Lemna gibba. L. gibba is unusual among angiosperms in that its roots are normally exposed to light during growth and contain chloroplasts. We have found that such roots transcribe rbcS genes and contain rbcS mRNA. We have used sequence-specific probes from the 3'-untranslated region of six rbcS genes from L. gibba to analyze the expression of the individual genes in different organs. All six genes were expressed in steady-state mRNA in fronds grown in constant white light. However, only five of these were easily detectable in steady-state mRNA isolated from roots of the same plants, and the relative expression of each gene varied between the roots and the fronds. In steady-state mRNA, SSU1 was found to be highly expressed in both roots and fronds, whereas SSU40B was expressed at low levels in the roots as compared with the fronds, and SSU5B RNA was barely detectable in the roots. The extremely low level of SSU5B RNA in steady-state root mRNA is likely to be a consequence of post-transcriptional events because this gene was transcribed at comparable rates in vitro in nuclei isolated from either roots or fronds. Localization of individual gene transcripts by in situ hybridization showed that SSU1 and SSU5B are expressed in the same cells in the fronds. Thus, the mechanism of differential expression is likely to involve an organ-specific post-transcriptional mechanism.